Performing different lives in Chaza Charafeddine’s series of Portraits - Taan, Yasmine Nachabe (Revelar: Revista de Estudos da Fotografia e Imagem, 2019)
An ongoing system of slavery supported by the Ministry of Labor in Lebanon is seen by human rights activists as a widespread staggering social issue that leaves a growing community of female migrant-domestic-workers in Lebanon with no legal rights to escape abusive employers and poor working conditions while enduring sexual, verbal and physical abuse on daily basis.Within the discourse of power, the Beirut-based artist, Chaza Charafeddine (born 1964) chose to destabilize this dynamic of power in Maidames, a series of portraits that depicts a number of domestic workers in Lebanon dressed up as TV celebrities and popular figures in glamorous settings. This paper examines how Charafeddine's portraits attempt to reverse roles by reshuffling the system of visual dynamics to offer an alternative, open dialogue for the purpose of negotiating identities. Play-acting, theatricality and props are evident throughout Charafeddine's portraiture practice. By portraying female domestic workers in assertive poses, confronting their viewer, Charafeddine aims at restoring their individuality. The women's performance in these portraits becomes the subject of the picture. Yet there is an inescapable hint of ambivalence, tension, even perversity beneath their cheery performance. Charafeddine's practice of portraiture raises questions about photography in relation to aesthetics and ethics that will be addressed in this paper. The work will be analyzed at the level of production and perception drawing from cross-disciplinary approaches related to art, sociology, and feminism within the context of the Middle East.